18(x+1)(x-1)=0

Simple and best practice solution for 18(x+1)(x-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18(x+1)(x-1)=0 equation:


Simplifying
18(x + 1)(x + -1) = 0

Reorder the terms:
18(1 + x)(x + -1) = 0

Reorder the terms:
18(1 + x)(-1 + x) = 0

Multiply (1 + x) * (-1 + x)
18(1(-1 + x) + x(-1 + x)) = 0
18((-1 * 1 + x * 1) + x(-1 + x)) = 0
18((-1 + 1x) + x(-1 + x)) = 0
18(-1 + 1x + (-1 * x + x * x)) = 0
18(-1 + 1x + (-1x + x2)) = 0

Combine like terms: 1x + -1x = 0
18(-1 + 0 + x2) = 0
18(-1 + x2) = 0
(-1 * 18 + x2 * 18) = 0
(-18 + 18x2) = 0

Solving
-18 + 18x2 = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 18x2 = 0 + 18

Combine like terms: -18 + 18 = 0
0 + 18x2 = 0 + 18
18x2 = 0 + 18

Combine like terms: 0 + 18 = 18
18x2 = 18

Divide each side by '18'.
x2 = 1

Simplifying
x2 = 1

Take the square root of each side:
x = {-1, 1}

See similar equations:

| 4(8-3y)=32-8(y+2) | | 36x^5-a^2x^3-36x^2+a^2= | | k/6-2=0 | | 4(b-3)-b=b-6 | | p/3=36 | | 1/2*4x-6y | | 13x-25=26x-113 | | 14x+27=25x+35 | | 2b=52 | | 5y^2-2y=0 | | (360-y)-2y=80 | | 1/4x-1/9x=5/18 | | X^48=110 | | m=Sexy | | 309/400.100 | | v^2+15v=-15 | | -(42x^2-x-5)= | | 5x-3x-2x=6 | | -x-5=20 | | 3000=1500x^3 | | 17x+3x=10 | | 4x+4y-x^2+xy-y^2+21=0 | | 39+(-24)-(15)= | | 0.4c^2-7c-25=0 | | T(2T+5)=6 | | 3r^2-7r-20=0 | | T-(2t+5)-5(1-2t)=2 | | x^2-8a^2-x=8a+ax-8ax | | a^2-3a+ab-3b=0 | | w^2-wd-56d^2=0 | | 6-2a-3b+ab=0 | | 3x(x-7)=(2x+8)(x-7) |

Equations solver categories